Riding simulator training induces a lower sympathetic response in riders than training with horses - Ille, N.; von Lewinski, M.; Aurich, C.; Erber, R.; Wulf, M.; Palme, R.; Greenwood, B.; Aurich, J. (Journal of Equine Veterinary Science, 2015)
Recently, equestrian riding simulators have become available for dressage, jumping, polo, or racing. In this study, we have compared salivary cortisol, heart rate, and heart rate variability (HRV) variables, standard deviation of beat-to-beat interval and root mean square of successive beat-to-beat differences, in 12 riders jumping a course of obstacles on a horse and on a riding simulator. Salivary cortisol concentrations from 60 minutes before to 60 minutes after simulator training were higher (P < .05) than those during training with a horse but did not change acutely with the simulated or real show jumping efforts. This indicates that the novel situation of simulator training was perceived as more stressful than routine training with a horse. Heart rate of the riders increased both on a horse and on a simulator (P < .001) but reached significantly higher values on the horse versus the simulator (175 ± 3 vs. 123 ± 5 beats/min, P < .01). Both HRV variables decreased (P < .001) during the simulated course and on a horse. From 30 minutes before to 30 minutes after the jumping tests, HRV variables were higher in association with the simulated course versus the course jumped with a horse (standard deviation of beat-to-beat interval, P < .05; root mean square of successive beat-to-beat differences, P = .056). The changes in heart rate indicate that simulator training required less physical effort than training on a horse. Based on differences in HRV, training with a horse was associated with a more pronounced sympathetic tone than simulator training. Although simulator training in principle mirrored the situation on a horse, the demands on a horse were more complex.